2019
DOI: 10.1108/oir-02-2018-0058
|View full text |Cite
|
Sign up to set email alerts
|

@Digital libraries: harnessing Twitter to build online communities

Abstract: Purpose The purpose of this paper is to investigate the types of roles that Twitter played in digital libraries (DLs) and their relationships in building DL online communities. Design/methodology/approach A mixed method analysis of DLs’ tweets was conducted to identify the usage, roles of Twitter in DL communities and relationships among the roles. Twitter data from 15 different DLs for one year were extracted, and an open coding analysis was performed to identify types of Twitter roles. Pearson correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Social media is a practical, low-cost method by which libraries can disseminate information as well as foster community engagement. Previous studies surrounding the use of social media in libraries have explored various aspects such as content (Shiri & Rathi 2013;Anderson 2015;Mon & Lee 2015;Joo et al 2018;Xie & Stevenson 2019;Joo et al 2020), stakeholder perceptions (Abidin et al 2013;Anwyll et al Winter 2013;Winn et al 2015;Cavanagh 2016;Shafawi & Hassan 2018;AlAwadhi & Al-Daihani 2019;Jones & Harvey 2019;Budu et al 2020;Pashootanizadeh & Rafie 2020;Williams et al 2021), and effective use strategies (Anwyll et al Fall 2013;Harmon & Messina 2013;Ramsey & Vecchione 2014;Smeaton & Davis 2014;Stone 2014;Valenza et al 2014;Mon 2015;Zou et al 2015;Peacemaker et al 2016;Rossmann & Young 2016;Bickford 2017;Gow 2017;Guevara 2018;Woodworth 2018;Fonseca 2019;Trucks 2019;Chaputula et al 2020). However, the majority of this literature has limited its focus to social media in the general sense or to individual platforms; thus, very little has been done to investigate and compare libraries' use of multiple platforms, particularly in-depth.…”
Section: Social Media Usage In Librariesmentioning
confidence: 99%
“…Social media is a practical, low-cost method by which libraries can disseminate information as well as foster community engagement. Previous studies surrounding the use of social media in libraries have explored various aspects such as content (Shiri & Rathi 2013;Anderson 2015;Mon & Lee 2015;Joo et al 2018;Xie & Stevenson 2019;Joo et al 2020), stakeholder perceptions (Abidin et al 2013;Anwyll et al Winter 2013;Winn et al 2015;Cavanagh 2016;Shafawi & Hassan 2018;AlAwadhi & Al-Daihani 2019;Jones & Harvey 2019;Budu et al 2020;Pashootanizadeh & Rafie 2020;Williams et al 2021), and effective use strategies (Anwyll et al Fall 2013;Harmon & Messina 2013;Ramsey & Vecchione 2014;Smeaton & Davis 2014;Stone 2014;Valenza et al 2014;Mon 2015;Zou et al 2015;Peacemaker et al 2016;Rossmann & Young 2016;Bickford 2017;Gow 2017;Guevara 2018;Woodworth 2018;Fonseca 2019;Trucks 2019;Chaputula et al 2020). However, the majority of this literature has limited its focus to social media in the general sense or to individual platforms; thus, very little has been done to investigate and compare libraries' use of multiple platforms, particularly in-depth.…”
Section: Social Media Usage In Librariesmentioning
confidence: 99%
“…Wellman and Gulia (1996) found that people receive several types of support from online communities, including informational support, emotional support, and companionship. While the research literature reflects the fact that Twitter can be a valuable source of information, it is also evident that it can play an important role in providing psychological and social support (Bell 2012;Cuddy, Graham, and Morton-Owens 2010;Xie and Stevenson 2019). Xie and Stevenson (2019) showed how Twitter plays a critical role in building libraries' communities by creating social identity and communicating social connections.…”
Section: Studies Of Social Media Usage In Public Librariesmentioning
confidence: 99%
“…Twitter is a social media application that has been launched since 2006 [5]. With social networking use surpassing web-based email utilizes in February 2009, a few about the connection are just not being created by humans.…”
Section: Literature Reviewmentioning
confidence: 99%